Re-Directing CD4+ T Cell Responses with the Flanking Residues of MHC Class II-Bound Peptides: The Core is Not Enough - Cole, David K. (Frontiers in Immunology, 2013)
Recombinant αβ T cell receptors (TCRs) recognise short peptides presented at the cell surface in complex with MHC molecules. There are two main subsets of αβ T cells: CD8+ T cells that recognise mainly cytosol-derived peptides in the context of MHC class I (pMHC-I), and CD4+ T cells that recognise peptides usually derived from exogenous proteins presented by MHC class II (pMHC-II). Unlike the more uniform peptide lengths (usually 8-13mers) bound in the MHC-I closed groove, MHC-II presented peptides are of a highly variable length. The bound peptides consist of a core bound 9mer (reflecting the binding motif for the particular MHC-II type) but with variable peptide flanking residues (PFRs) that can extend from both the N- and C-terminus of the MHC-II binding groove. Although pMHC-I and pMHC-II play a virtually identical role during T cell responses (T cell antigen presentation) and are very similar in overall conformation, there exist a number of subtle but important differences that may govern the functional dichotomy observed between CD8+ and CD4+ T cells. Here, we provide an overview of the impact of structural differences between pMHC-I and pMHC-II and the molecular interactions with the TCR including the functional importance of MHC-II peptide flanking residues. We consider how factors such as anatomical location, inflammatory milieu and particular types of APC might, in theory, contribute to the quantitative (i.e. pMHC ligand frequency) as well as qualitative (i.e. variable PFR) nature of peptide epitopes, and hence offer a means of control and influence of a CD4+ T cell response. Lastly, we review our recent findings showing how modifications to these flanking regions modify CD4+ T cell antigen recognition. These findings may have novel applications for the development of CD4+ T cell peptide vaccines and diagnostics.